Allah yang Mati: Sebuah Kajian Soteriologis atas Paradoks Kematian Yesus Kristus - Yustinus, Yustinus (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
Jesus' death on the cross presents a paradox between God's eternal nature and the reality of a dying God, sparking intense debate in pluralistic societies. This study analyzes the relationship between Jesus' divinity and death from a soteriological perspective using systematic theology and historical-biblical analysis. The research demonstrates that the doctrines of communicatio idiomatum and Chalcedonian Christology resolve this paradox by maintaining the integrity of both natures in one Divine Person of Jesus. The findings reveal that Jesus' death in human nature constitutes the ultimate expression of God's saving love. Precisely because Jesus is God, His sacrifice is able to redeem all humanity, while His humanity enables this redemptive event to occur. These findings not only strengthen the theological foundation of redemption doctrine but also provide a relevant resolutive framework for contemporary dialectics about Christ's identity. The theological implications require the church to embody cruciform spirituality through practices of kenosis and solidarity with the suffering.AbstrakKematian Yesus di atas salib menghadirkan paradoks antara natur Allah yang kekal dan realitas Allah yang mati, serta memicu perdebatan intens dalam masyarakat yang plural. Penelitian ini menganalisis relasi keilahian dan kematian Yesus dalam perspektif soteriologis melalui pendekatan teologi sistematis dan analisis historis-biblis. Kajian membuktikan bahwa doktrin communicatio idiomatum dan kristologi Kalkedon menyelesaikan paradoks ini dengan mempertahankan integritas kedua natur dalam satu Pribadi Ilahi Yesus. Temuan penelitian mengungkap bahwa kematian Yesus dalam natur manusia justru menjadi puncak pernyataan kasih Allah yang menyelamatkan. Hanya karena Yesus adalah Allah, maka pengorbanan-Nya sanggup menebus semua manusia, sementara kemanusiaan-Nya memungkinkan peristiwa penebusan itu terjadi. Temuan ini tidak hanya memperkuat fondasi teologis doktrin penebusan, tetapi juga memberikan kerangka resolutif yang relevan bagi dialektika kontemporer tentang identitas Kristus. Implikasi teologisnya menuntut gereja untuk menghidupi spiritualitas salib melalui praktik kenosis dan solidaritas dengan mereka yang menderita.